Current Tissue Molecular Markers in Colorectal Cancer: A Literature Review. (29th October 2017) - Peluso, Gaia; Incollingo, Paola; Calogero, Armando; Tammaro, Vincenzo; Rupealta, Niccolò; Chiacchio, Gaetano; Sandoval Sotelo, Maria Laura; Minieri, Gianluca; Pisani, Antonio; Riccio, Eleonora; Sabbatini, Massimo; Bracale, Umberto Marcello; et al.
Abstract : Background . Colorectal cancer (CRC) is one of the most spread neoplasia types all around the world, especially in western areas. It evolves from precancerous lesions and adenomatous polyps, through successive genetic and epigenetic mutations. Numerous risk factors intervene in its development and they are either environmental or genetic. Aim of the Review . Alongside common screening techniques, such as fecal screening tests, endoscopic evaluation, and CT-colonography, we have identified the most important and useful biomarkers and we have analyzed their role in the diagnosis, prevention, and prognosis of CRC. Conclusion . Biomarkers can become an important tool in the diagnostic and therapeutic process for CRC. But further studies are needed to identify a noninvasive, cost-effective, and highly sensible and specific screening test for their detection and to standardize their use in clinical practice.